PERANCANGAN PENGUKURAN PERFORMANCE OF BUSINESS PROCESS DI PT AJINOMOTO INDONESIA MOJOKERTO FACTORY DENGAN MENGGUNAKAN METODE "THE PERFORMANCE PRISM" - Mahmud Tontowi; Patdono Suwignjo (Jurnal Teknobisnis, 2005)
The performance measurement of an organization  recently becomes a trend for some reasons. First, the company or the  organization can estimate the efficient use of its resources. Secondly the company can plan future target performance more realistically in relation to the existing coundition. Thirdly, the company can apply proper strategies to improve the performance on the basic of actual achievement and expected performance. Until recently PT Ajinomoto Indonesia Mojokerto has not conduct holistic performance measurement. The measurement is conducted partially in each department. The method of performance measurement applied in this research is "The Performance Prism " focusing on stakeholders satisfaction which is a method developed in response to the previous methods such as Balance scorecard. This method deals with 5 aspects: stakeholders satisfaction, stakeholders Contributions, Strategies, Processes, and Capabilities. This reflects the facets of three — dimentional prism. The performance measurement of PT Ajinomoto Indonesia Mojokerto Factory using the Performance Prism obtains 28 Key Performance Indicator (KPI) for stakeholders Customer, Investor, Supplier, Employee and Community. Analitycal Hierarching Process (AHP) is applied to KPI. Having scared using OM4X the research results 14 KPI categorized as good in green 4 KPI is fair in yellow, and 10KPI is bed in red. The aggregate value is 5,6 showing fairly good infair condition yellow.